Analisis Manajemen Pemasaran pada Usaha Kecil dan Menengah (UMKM): Studi pada Produk Kuliner Tradisional “Kue Rotikap” - Izha Fadlam Jeffy; Nadia Ananta; Cici Suciati; Nur Hikmah (CV Global Research Publication, 2026)
This study aims to analyze the marketing management strategies implemented by small and medium enterprises (MSMEs) “Kue Rotikap” in Indonesia. The main focus of the research is to identify effective marketing strategies, using the 4P approach, namely place, price, promotion, and product, which are in accordance with the characteristics of the business. Using a descriptive qualitative approach, primary data was collected through interviews and direct observation, which provided an in-depth understanding of the challenges faced by MSMEs in dealing with market dynamics. The results of the research “Kue Rotikap” by using the 4P marketing mix principles, namely place, price, promotion, and product. By offering many variants of product flavors, affordable prices, strategic locations and promotional systems that utilize online media such as Instagram and WhatsApp, with quality products, competitive prices, wide distribution channels, and proper promotion, this business can continue to grow and compete in the MSME market.